Rio (1992) to Glasgow (2021): Three decades of inadequate mitigation of climate change and its slow onset effects - Stavi, Ilan (Frontiers in Environmental Science, 2022)
This study reviews the global increase in atmospheric greenhouse gas (GHG) concentrations, including carbon dioxide (CO2), methane (CH4), and nitrous oxide (N2O), alongside the accelerated climatic change and its slow onset effects (or events) between 1992–2021. The establishment of the United Nations Framework Convention on Climate Change (UNFCCC) in 1992, and the simultaneous UN Earth Summit in Rio de Janeiro, generated the international efforts to tackle climatic change. Over the years, the UNFCCC-Conference of the Parties (COP) has led the efforts in climate change mitigation and adaptation, with many sequential meetings across the world. Three decades later, at the COP26 meeting in Glasgow in 2021, it is evident that climate change impacts have substantially worsened. Despite some uncertainties, it seems that over the last three decades, the climate change slow onset events, including (1) increasing temperatures, (2) glacial retreat, (3) sea level rise, (4) ocean acidification, (5) soil salinization, (6) land and forest degradation, (7) loss of biodiversity, and (8) desertification, have substantially exacerbated. Simultaneously, other (non-GHGs related) anthropogenic impacts, including habitat fragmentation, land-use and sea-use change and misuse, species overexploitation, environmental pollution, infrastructure constructions, and urbanization, have considerably increased. With the aim of achieving the Shared Socio-Economic Pathways 1.9 (SSP1-1.9) or SSP1-2.6 ultimate goals – keeping global warming in 2100 below 1.5 °C or 2.0 °C, respectively, compared to preindustrial levels – it may still be possible to avoid climate change’s irreversible tipping points. To reach this target, policymaking must become more decisive and proactive, with continuous risks assessment, frequent monitoring of outcomes and their compatibility to goals, implementing practical legislation tools, and assigning specific financial instruments, aimed at effectively tackling climate change slow onset events and related environmental issues. Substantial efforts should be invested in boosting climate change mitigation, while simultaneously targeting effective climatic change adaptation measures and promoting environmental conservation and restoration. Relying on tools such as the UN Sustainable Development Goals (SDGs) will sustain provisioning, supporting, regulating, and cultural ecosystem services, thus improving water-, food-, environmental-, energy-, economic-, health-, and governance-security, while lessening the risks of social unrest, violent conflicts, mass migration, and other humanitarian catastrophes.